The acute effects of static stretching on peak force, peak rate of force development and muscle activity during single- and multiple-joint actions in older women - Gonçalves, Raquel [UNESP]; Gurjão, André Luiz Demantova [UNESP]; Jambassi Filho, José Claudio [UNESP]; Farinatti, Paulo de Tarso Veras; Gobbi, Lilian Teresa Bucken [UNESP]; Gobbi, Sebastião [UNESP] (Taylor & Francis, 2013)
The present study investigated the acute effects of static stretching on peak force, peak rate of force development and integrated electromyography (iEMG) in 27 older women (65 ± 4 years; 69 ± 9 kg; 157 ± 1 cm; 28 ± 4 kg · m-2). The participants were tested during two exercises (leg press and knee extension) after two conditions: stretching and control. The data were collected on four days (counterbalanced with a 24-hour rest period). In the stretching condition, the quadriceps muscle was stretched (knee flexion) for three sets of 30 s with 30 s rest intervals. No significant difference was detected for peak force and peak rate of force development during the single- and multiple-joint exercises, regardless of the following interactions: condition (stretching and control) vs. time (pre x post x 10 x 20 x 30 minutes post; P > 0.05) and exercise vs. time (P > 0.05). Additionally, no significant interaction was found for the iEMG activity (condition vs. time; P > 0.05) in the single- and multiple-joint exercises. In conclusion, a small amount of stretching of an agonist muscle (quadriceps) did not affect the peak force, peak rate of force development and EMG activity in older women during single- and multiple-joint exercises. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: aging; isometric force-time curve; performance; warm-up; aged; controlled clinical trial; controlled study; electromyography; exercise; female; human; joint; leg; middle aged; muscle isometric contraction; muscle strength; physiology; quadriceps femoris muscle; randomized controlled trial; stretching exercise; Aged; Electromyography; Exercise; Female; Humans; Isometric Contraction; Joints; Lower Extremity; Middle Aged; Muscle Strength; Muscle Stretching Exercises; Quadriceps Muscle